2012
DOI: 10.1128/aac.06262-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dimerization on the Structure and Biological Activity of Antimicrobial Peptide Ctx-Ha

Abstract: It is well known that cationic antimicrobial peptides (cAMPs) are potential microbicidal agents for the increasing problem of antimicrobial resistance. However, the physicochemical properties of each peptide need to be optimized for clinical use. To evaluate the effects of dimerization on the structure and biological activity of the antimicrobial peptide Ctx-Ha, we have synthesized the monomeric and three dimeric (Lys-branched) forms of the Ctx-Ha peptide by solid-phase peptide synthesis using a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 42 publications
1
47
0
2
Order By: Relevance
“…In contrast, despite the fact that a significant decrease of the MIC values was not observed, the preassembly of multiple copies of BP100 and BP143 did have an important effect on the bactericidal activity. The results showed that the carbopeptides 1 – 3 were significantly more potent than the corresponding monomers, which is in agreement with previous studies [3435]. This ability to kill the bacteria rapidly confers them a greater capacity to control bacterial cell growth, which may be important for their future potential use as bactericidal agents.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, despite the fact that a significant decrease of the MIC values was not observed, the preassembly of multiple copies of BP100 and BP143 did have an important effect on the bactericidal activity. The results showed that the carbopeptides 1 – 3 were significantly more potent than the corresponding monomers, which is in agreement with previous studies [3435]. This ability to kill the bacteria rapidly confers them a greater capacity to control bacterial cell growth, which may be important for their future potential use as bactericidal agents.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, great differences are seen between the native and P14C peptides although they have the same charge and hydrophobicity. The effects of dimerization of AMP, CtxHa, have recently been reported (Lorenzon et al 2012). The difference in the biological activity of the monomer and dimeric peptide could not be explained by different mechanisms of action, secondary structure or proximity of the peptide chains and may be sequence dependent.…”
Section: Structural Analysismentioning
confidence: 97%
“…Although the mechanism of AMP action is unknown and pore formation in cell membranes may be responsible for lytic ability, it is well established that AMP interact directly with the cell membrane surface and are able to enter the lipid bilayer, resulting in cell membrane disruption and leakage of cytoplasmic components which leads to killing of microbes (Lee et al 2010;Izadpanah and Gallo 2005;Lorenzon et al 2012;Sani et al 2013). AMP have attracted much attention as an alternative to antibiotics because of their effect against bacterial infections and drug resistant bacteria (Juba et al 2013;AnayaLopez et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…This sequence shows a significant increase in antimicrobial activity when the two chains are linked by a central disulfide bond19. In contrast, the ability of another peptide Ctx-Ha to inhibit the growth of microorganisms is reduced upon dimerization while its hemolytic activity increased20.…”
mentioning
confidence: 99%